The Case of Atypical Sexual Attractiveness in a Male Domestic Dog—A Case Study - Martyna Woszczyło; Antoni Szumny; Jacek Łyczko; Tadeusz Jezierski; Paulina Krzemińska; Izabela Szczerbal; Marek Świtoński; Wojciech Niżański; Michał Dzięcioł (Animals, 2021)
During the ovarian cycle in domestic dogs, females do not accept males during the first days of estrus but become attractive to males from the beginning of proestrus, with this attractiveness persisting until the end of the estrus phase. It is believed that increased estradiol is responsible for the female attractiveness to the males. In this paper we describe the case of strong, but atypical attractiveness of a castrated male to various, adult, intact males, influenced by the emitted semiochemical signals. Any significant changes in the level of hormones typically involved in the process connected with estrus and responsible for sexual arousal in the males were assessed. The case animal was a 4 year old castrated male Border Collie that was extremely attractive to various males, which presented high levels of sexual arousal, with intensive sniffing and licking of the preputial area, specific vocalization, increased salivation and, finally, mating attempts. Clinical examination of the castrated male revealed a lack of testes in the scrotum and abdominal cavity confirmed by USG. Laboratory tests indicated basal levels of estradiol, testosterone, and progesterone (15.23 pg/mL, <0.05 ng/mL, 0.25 ng/mL), and sex was confirmed via cytogenetic and molecular analysis. Chemical analysis (HS-SPME) of the urine indicated a huge similarity to the profile obtained from a bitch in estrus, with an elevated level of acetophenone, which has been previously postulated in the literature as being a characteristic of the estrus phase in female domestic dogs. This case presented very atypical sexual attractiveness, particularly when taking into account the basal levels of hormones which, according to current knowledge, are responsible for the creation of attractiveness. As a hypothesis requiring verification, we propose the idea of involvement of other hormones in the creation of incidental attractiveness or increased production of compounds responsible for attractiveness (sex pheromones) resulting from metabolic events unrelated to reproductive processes. To our knowledge it is the first described case presenting this phenomenon, which, with more detailed study, could shed new light on the process of creation of sexual attraction in the domestic dog.